2023
DOI: 10.1007/s43939-023-00045-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research and effect on mechanical and wear properties of aluminium based composites reinforced with Zn/Sic particles

Abstract: In this investigation, Al-/Zn/SiC composite with various weight percentages of SiC were manufactured via powder metallurgy (PM) route. Using the powder metallurgy approach, composites are created by changing the amount of SiC in the range of 5–15% by weight respectively. Under fretting wear test, the tribological characteristics of these composite materials were examined at load (5N, 10N, 15N), constant control parameters like that of frequency (20 Hz), temperature (at room temperature), stroke length (0.50 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
0
0
Order By: Relevance
“…The decrease in COF during sliding wear with an increase in load is due to the accumulation of wear debris in the spaces between the pin and disc, resulting in a reduced adequate depth of penetration, and when the load is exerted, causes the metal surfaces to oxidize more quickly, eventually changing the mechanism from two-body to three-body wear. The current result is in good agreement with the study carried out by [46].…”
Section: Analysis and Discussion Of Results Of Cofsupporting
confidence: 93%
“…The decrease in COF during sliding wear with an increase in load is due to the accumulation of wear debris in the spaces between the pin and disc, resulting in a reduced adequate depth of penetration, and when the load is exerted, causes the metal surfaces to oxidize more quickly, eventually changing the mechanism from two-body to three-body wear. The current result is in good agreement with the study carried out by [46].…”
Section: Analysis and Discussion Of Results Of Cofsupporting
confidence: 93%
“…The alloying of a trace amount of zinc (Zn) to the Al-Si alloy results in a decrease in the eutectic needle size and an improvement in the homogeneity of the matrix [5] . Dhakar et al [6] reported that the alloying of Zn with the hypereutectic Al-Si alloy results in the formation of high-density precipitates in the microstructure, which significantly results in an increase in tensile strength, wear resistance, and hardness [7,8] .…”
Section: Introductionmentioning
confidence: 99%